A detailed energy analysis of a novel evaporator with latent thermal energy storage ability. (25th January 2022) - Mselle, Boniface Dominick; Zsembinszki, Gabriel; Vérez, David; Borri, Emiliano; Cabeza, Luisa F.
Highlights: A detailed energy analysis of a novel evaporator-TES module was carried out. The energy storage contribution in each material was evaluated. More than 54% of the total energy was stored in the PCM despite its low mass. The effective charging of the module was observed between −2 °C and 7 °C. The charge level varies depending on energy supply and demand conditions. Abstract: The direct integration of phase change materials (PCM) into refrigeration and air conditioning systems through compact modules is an identified literature gap. In response to the literature gap, this paper provides a detailed energy analysis of a novel compact thermal energy storage module, that allows its direct integration into a refrigeration system as the evaporator. The study addresses key aspects of thermal energy storage (TES) and heat transfer mechanism that complement the previous analyses of the novel concept. Here the total energy stored in the module (including in all auxiliary parts), the charging/discharging power, and the behaviour of the module when used as a TES module and as a heat exchanger (HEX) are assessed. The results demonstrate the feasibility of the module to work as a TES and as a HEX. When working as a TES, complete charging and discharging was achieved, and 54% of the total energy was stored in the PCM although the PCM only accounts for around 14% of the total mass. Moreover, the highest charging/discharging power was obtained within the temperature range where most of the phase change occurred. When the module works as a HEX, it initially charges/discharges partially until a thermal equilibrium is achieved and the level of charge responds to the variation in the energy supply and demand.